Ethnic-racial relations on the Pedagogical Master Plans of undergraduate teaching training degree courses in Biology in São Paulo (Práxis Educativa, 2022)
The National Curriculum Guidelines for the Education of Ethnic-Racial Relations and the Teaching of Afro-Brazilian and African History and Culture establishes that pedagogical plans of undergraduate teaching training degree courses must contain education of ethnic-racial relations. To verify which approaches are found in this type of document, 14 Pedagogical Master Plans of São Paulo State public undergraduate teaching training courses in Biology were analyzed. Based on the content analysis, it was verified that the Guidelines were explicitly mentioned in six of the Master Plans and that the critical position associated with the use of biological knowledge in the face of racial discrimination was placed as competence of the graduated student in five of them. It was also observed a variety of contents associated with the education of ethnic-racial relations, but these contents were concentrated on pedagogical and/or humanity areas, marginalizing biological-specific areas.Keywords: Teacher training. Curriculum. Coloniality. Biology teaching.